Tourist revisit intention: does image affect their preference? - Ari Arisman; Raisa Hillia Aini Syifa; Andina Eka Mandasari; Mohammad Soleh Soeaidy (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Tourism is a cross-cultural encounter that happens every day. Thus, the life cycle of the tourism industry is represented by first-time tourists and tourists who make return visits to a destination. This study aims to examine the relationship between destination image and revisit intention through utilitarian value, hedonic value, and preference. The population of this study consisted of domestic tourists who traveled to three main destinations, namely Bandung, Yogyakarta, and Bali. The sample was considered by the criteria as many as 333 tourists were asked to answer the questionnaire. The method used in this research is a survey with a Structural Equation Modeling (SEM) analysis technique. The results revealed that destination image positively affects utilitarian and hedonic values. Utilitarian and hedonic values are positively related to preference. Preference is positively related to revisiting intention. The results of this study make a theoretical contribution by deepening the understanding of revisit intention. In addition, this study makes a practical contribution to the tourism industry. Limitations and future research directions are included at the end of the article.